CONTRIBUTION OF THE MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) SECTOR TO THE INDONESIAN ECONOMY - Hasibuan, Indra Mualim; Erianto, Ridho; Sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2024)
Micro, Small and Medium Enterprises are one of the backbones of the economy. Based on experience, the MSME sector can survive when an economic crisis occurs and becomes a support for the country's economy. Many MSMEs provide opportunities for the Indonesian economy to improve. Because the MSME sector contributes to the gross domestic product sector and employment. This research is qualitative research using a literature study approach. The aim of the research is to determine the contribution of MSMEs to GDP and employment in Indonesia. Research results in 2015 the MSME sector contributed to GDP by 57%, in 2016 by 57.2%, in 2017 by 57.1%, in 2018 by 57.8%, in 2019 by 60.3%, in 2020 by 37 .3%, in 2021 it will be 61.7%, and in 2022 it will be 60.1%. Then the contribution of MSMEs to labor absorption in 2015 was 96.71%, in 2016 it was 97.4%, in 2017 it was 96.82%, in 2018 it was 97%, in 2019 it was 96.92%, in 2020 it was 57%. .92%, in 2021 it will be 97%, and in 2022 it will be 97%.